Alarming epidemic of rice tungro disease in North-West India - J. SINGH1, S.S. CHEEMA3; S.S. SOKHI3, A. VARMA1, F.R. NIAZI1, I. DASGUPTA2 (Indian Phytopathology, 2002)
Rice tungro virus (RTV) was detected in diseased rice crops in Gurdaspur and Amritsar districts, Punjab, India between Aug-Sep. 1998.